Interaction of the v-Rel oncoprotein with cellular transcription factor Sp1. - Sif, S (1994)
We previously showed that v-Rel, the oncoprotein of the avian retrovirus Rev-T, can increase expression from promoters containing binding sites for the cellular transcription factor Sp1 in chicken embryo fibroblasts (S. Sif, A.J. Capobianco, and T.D. Gilmore, Oncogene 8:2501-2509, 1993). In those experiments, v-Rel appeared to increase the transactivating function of Sp1; that is, v-Rel stimulated transactivation by a GAL4-Sp1 protein that lacked the Sp1 DNA-binding domain. We have now shown that in vitro-synthesized v-Rel and GAL4-Sp1 form a complex that can be immunoprecipitated with either anti-Sp1 or anti-v-Rel antiserum. We have also shown that a glutathione S-transferase (GST)-Sp1 fusion protein can specifically interact with in vitro-translated v-Rel and with in vivo-synthesized v-Rel from transformed chicken spleen cells. In addition, we have found that the abilities of wild-type and two mutant forms of v-Rel to increase transactivation by Sp1 in vivo correlate with their abilities to interact with Sp1 in vitro. The sequences important for the interaction of v-Rel with Sp1 in vitro have been mapped to the first 147 amino acids of v-Rel. Other Rel proteins, such as c-Rel, RelA, p52, and p50, were also able to form a complex with Sp1 in vitro. These results suggest that v-Rel increases expression from Sp1 site-containing promoters by functionally interacting with Sp1 and that cellular Rel proteins and Sp1 are likely to interact to influence transcription from natural promoters.